KONFLIK ANTARA FATWA-FATWA ZAKAT KE ATAS WANG CARUMAN DALAM KUMPULAN WANG SIMPANAN PEKERJA (KWSP) DI MALAYSIA: ANALISIS FIQH: Conflicts Among Fatwas of Zakah on Employees Provident Fund (EPF) in Malaysia: Fiqh Analysis - Haji Abdullah, Luqman; Rosele, Muhammad Ikhlas (Jurnal Syariah, 2019)
The fatwas of zakah on EPF in Malaysia are different from one state to another and this cause confusions which need some clarification. This article intends to analyze the fatwas to identify factors of that differences and to find juristic justification of the fatwas. This study is qualitative in nature and will be depending heavily on the fiqh literatures and the texts of fatwas. This study found out that the differences of fatwa rised from the application of the condition of ownership and the technical application surround it.